2004
DOI: 10.1590/s0102-33062004000300015
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de plantas jovens de Myracrodruon urundeuva Allemão (Anacardiaceae) sob diferentes regimes hídricos

Abstract: RESUMO -(Crescimento de plantas jovens de Myracrodruon urundeuva Allemão (Anacardiaceae) sob diferentes regimes hídricos). Objetivou-se avaliar o crescimento das plantas jovens cultivadas em casa de vegetação submetidas a três regimes hídricos: 25, 50 e 75% da capacidade de campo (cc) em duas épocas de avaliação (30 e 60 dias). As variáveis observadas foram: altura de planta, massa seca, alocação de biomassa e densidade estomática. Os três regimes hídricos não exerceram influência no comprimento da raiz. A raz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1
22

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 7 publications
4
21
1
22
Order By: Relevance
“…Similar results were observed with C. ferrea (pau-ferro) seedlings (LENHARD et al, 2010) cultivated at 70%, 40%, and 12.5% field capacity and under saturation conditions; with Myracrodruon urundeuva (aroeira) seedlings (FIGUEIRÔA et al, 2004) cultivated at 75%, 50%, and 25% field capacity; and with Guazuma ulmifolia (mutambo) seedlings (SCALON et al, 2011) cultivated at 100%, 50%, 25%, and 12.55% field capacity.…”
Section: Discussionsupporting
confidence: 77%
“…Similar results were observed with C. ferrea (pau-ferro) seedlings (LENHARD et al, 2010) cultivated at 70%, 40%, and 12.5% field capacity and under saturation conditions; with Myracrodruon urundeuva (aroeira) seedlings (FIGUEIRÔA et al, 2004) cultivated at 75%, 50%, and 25% field capacity; and with Guazuma ulmifolia (mutambo) seedlings (SCALON et al, 2011) cultivated at 100%, 50%, 25%, and 12.55% field capacity.…”
Section: Discussionsupporting
confidence: 77%
“…The long-term persistence of cotyledons in tropical woody species has been reported in several studies, as in Cabral et al (2004), who verified that cotyledons remained for 120 days attached to plants of Tabebuia aurea. Similarly, studies have shown that seedlings of M. urundeuva are able to maintain the cotyledons for a period of 90 days (Figueirôa et al 2004), while K. coriacea cotyledons may remain attached to the plant for up to six months (Nardoto et al 1998). The authors highlighted the great reliance on this organ in the initial growth of these species.…”
Section: Discussionmentioning
confidence: 93%
“…Villagra e Cavagnaro (2006) encontraram reduções na matéria seca de todos os órgãos e total de plantas jovens de P. argentina e P. alpataco submetidas a déficit hídrico por 96 dias. À semelhança deste resultado, Figueirôa et al, (2004) observaram reduções significativas nos tratamentos com 50 e 25% da capacidade de campo em relação à matéria seca das folhas, caule, raízes e total em plantas jovens de Myracrodruon urundeuva Allemão apenas aos 60 dias, não tendo encontrado diferenças significativas aos 30 dias de aplicação dos tratamentos.…”
Section: Matéria Seca Das Folhas Caule E Raízesunclassified